SOCIAL PARTNERSHIP IN LABOR: REGULATORY FRAMEWORK AND BALANCE OF INTERESTS - Zhakupov , Руслан Елюбаевич; Khassenov, Муслим Ханатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
This article considers the issues of legal mechanism of social partnership in labor sphere.